KONSTRUKSI SOSIAL AJARAN NYELENEH PADA MASYARAKAT SAMIN DI DUSUN JEPANG KECAMATAN MARGOMULYO KABUPATEN BOJONEGORO JAWA TIMUR - -, Annisa; Kebayantini, Ni Luh Nyoman; Krisna Aditya, I Gst.Ngr. Agung (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2021)
The Samin community is a society that adheres to the teachings of Saminism which was initiated by Samin Surosentiko. The Samin community has teachings that are considered odd by outsiders. This study aims to explain social construction and changes in teachings that are considered eccentric in the Samin community in the Jepang Hamlet, Margomulyo District, Bojonegoro Regency. The theoretical basis used in this research is Peter L. Berger's theory of social construction. the eccentric teachings of the Samin community are the result of Samin Surosentiko's externalization to fight against the invaders The construction of eccentric teachings on the Samin community in the Jepang Hamlet of has not been legitimized since knowing the independence of Indonesia in 1965.The teachings of Samin that are still carried out by the Samin community in the Jepang Hamlet are the teachings of kebatinan/morality. Keywords: eccentric teachings, social construction, changes in the Samin community.